The inverse relation between self-esteem and anticipatory coping - Newby-Clark, Ian R. (University of Waterloo, 1999)
At one time or another, we all experience psychologically aversive events that we cannot, or have failed to, avoid. The effects of such events can sometimes be ameliorated by preparatory thoughts and behaviour (i.e., anticipatory coping). I propose that self-esteem is inversely related to anticipatory coping. High self-esteem (HSE) people can be distinguished from low self-esteem (LSE) individuals on the related dimensions of optimism and caution. HSE people are relatively optimistic and LSE people are comparatively pessimistic and cautious. I hypothesize that LSE individuals may more readily anticipate negative occurrences and less readily anticipate positive occurrences than HSE people. Such self-esteem differences would afford LSE people more opportunity to prepare for disagreeable future episodes. I hypothesize that LSE individuals, arguably due to their cautious nature, engage in more anticipatory coping than HSE people. Also, I explore the relation between self-esteem and anticipatory coping when a disagreeable episode is more or less probable. Compared to an improbable aversible event, HSE and LSE people will prepare more if it is relatively probable. LSE people, though, will vary their preparation behaviour less than HSE individuals. Specifically, LSE people will err on the side of caution and prepare for an improbable aversive event more than will HSE individuals. In Study 1, I tested my hypothesis that LSE people more readily anticipate negative future events than HSE people (and vice versa for positive events). Using a response latency paradigm, I found that LSE people more quickly thought of negative future events than HSE people. HSE people were faster in thinking of positive future episodes. In Study 2, I investigated self-esteem differences in anticipatory coping. Participants were instructed to imagine that one good and one bad event was certain to occur. They then described each event and indicated how they would cope with the negative occurrence. Reinforcing the findings of the first study, people with low self-regard envisioned negative future occurrences in greater detail than did high self-esteem people. There were no self-esteem differences in anticipatory coping, however. In Study 3, the probability of an impending aversive event was varied and self-esteem differences in anticipatory coping were investigated. Participants were faced with either a low or high probability of engaging in a painful task. They were then informed of a previously successful preparatory strategy for reducing pain and given the opportunity to use it. The amount of time participants dedicated to preparation for the aversive event was measured. Overall, participants in the high probability condition prepared more than those in the low probability condition. Compared to HSE people, LSE individuals were relatively insensitive to the probability of the aversive event. The amount of time LSE participants dedicated to preparation for the aversive event did not significantly differ between the high and low probability conditions, whereas HSE individuals' preparation time did. HSE people prepared more in the high probability condition than in the low probability condition. In the low probability condition, LSE participants prepared more for the painful episode than HSE people. The consequences of the anticipatory coping findings are discussed.
Keywords: Harvested from Collections Canada